'It's not a Muslim ban!' Indirect speech acts and the securitisation of Islam in the United States post-9/11. Issue 1 (2nd January 2018) - Eroukhmanoff,
Abstract : ABSTRACT According to the Copenhagen School, a political issue is prioritised, or 'securitised', when an audience accepts a speech act with a particular security grammar pointing to the dangerous nature of the threat and calling for extraordinary security measures. This article probes the opposite: what if not saying 'security' and instead saying 'friend' also contributes to the securitisation? I explore this logic with the ways in which Islam has been securitised in the United States from the Bush administration to the beginning of the Trump administration and offer an analysis of what this article calls the 'indirect securitisation of Islam.' Drawing on the philosophy of language of John Searle, an indirect securitisation is one that is successful through indirect securitising speech acts, that is, utterances that comprise two illocutions, one direct and one indirect, with the latter being the 'real' request of the utterance. Using covert forms of speech such as indirect speech acts enables elite speakers to 'deny plausibility' and claim they are not securitising (or 'the least racist person' as Trump claims), thereby 'saving face.' Indirect securitising speech acts are therefore an important strategic tool in elite actors' securitising playbook. The article seeks to make sense of a climate of American politics that seem ungoverned by conventional rules of speech by offering a timely study of how political leaders can 'have their cake and eat it too' in matters of national security.